2008
DOI: 10.1007/s10404-008-0316-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ionic concentration on electrokinetic instability in a cross-shaped microchannel

Abstract: This paper performs numerical and experimental investigations into electrokinetic instability (EKI) effects to accomplish mixing of multiple solutions with different electric conductivities in a cross-shaped microchannel. This study considers two multiple-species, namely two aqueous electrolyte solutions and three electrolyte solutions with conductivity ratios ranging between 1 and 10, respectively. A stratified flow condition is formed when the intensity of the applied DC electrical field is below a certain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…It is not the purpose of the present study to provide a definite answer regarding the generating mechanism question, rather our main motivation for using a simple flow-focusing geometry was to explore the possibility of attaining a region of constant strainrate by making use of opposing lateral fluid streams that shape a third inlet stream flowing perpendicularly to the lateral entrances. A similar geometry has been used by Luo [16] to explore electrokinetic instability effects to promote mixing. The extensional flow in such a device is studied in detail by Oliveira et al [17].…”
Section: Introductionmentioning
confidence: 98%
“…It is not the purpose of the present study to provide a definite answer regarding the generating mechanism question, rather our main motivation for using a simple flow-focusing geometry was to explore the possibility of attaining a region of constant strainrate by making use of opposing lateral fluid streams that shape a third inlet stream flowing perpendicularly to the lateral entrances. A similar geometry has been used by Luo [16] to explore electrokinetic instability effects to promote mixing. The extensional flow in such a device is studied in detail by Oliveira et al [17].…”
Section: Introductionmentioning
confidence: 98%
“…A number of authors have used this type of configuration as passive micro-mixers (Jensen 1998;Knight et al 1998) and it has been shown that mixing times can be controlled and reduced by adjusting the pressure ratio between the main inlet stream and the lateral sheath streams (Jensen 1998). Luo (2009) explored electrokinetic instability effects to promote mixing. Another widely explored application that makes use of flow-focusing micro-devices is the production of droplets with narrow size distribution, whose sizes are tailored by the flow-rate ratio of the two immiscible fluids (Anna, Bontoux & Stone 2003;Garstecki, Stone & Whitesides 2005;Anna & Mayer 2006;Nie et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“… proposed that critical strength of electric field for EKI flow can be significantly decreased in coated micro‐channels. According to the research by Luo , the injection configuration of solutions has significant effect on the electrokinetic instability. The effect is strongest, when conductivity gradients of the mixed solutions are oriented in opposing directions instead of being aligned.…”
Section: Mixingmentioning
confidence: 99%